(untitled) (Global Conference on Multidisciplinary Research and Innovation, 2026)
The article explores the dialogue of genres between English and Uzbek drama, focusing on the works of Richard Brinsley Sheridan and Erkin Vohidov. The study examines how classical English comedic conventions interact with contemporary Uzbek dramaturgy, emphasizing structural, stylistic, and thematic features. Particular attention is paid to character construction, plot development, and the integration of comedic and tragic elements. The research highlights the influence of historical, social, and cultural contexts on genre formation in both traditions. It reveals both universal genre patterns and national-specific features, showing how classical and modern dramaturgical strategies can coexist and mutually enrich each other. The findings have practical significance for literature education, theatrical productions, cross-cultural communication, and comparative literary studies.